Vitamin D Levels in Growth-Paining Children - Günbey, Ömer; Gürgöze, Metin Kaya; Günbey, Fatma Betül (My University, 2024)
The most common cause of non-inflammatory recurrent musculoskeletal pain in children is growing pains. History and physical examination are often sufficient to diagnose these patients. Since the exact etiology is not known, different treatments can be applied. The effect of vitamin D levels on children with growing pains was investigated. Clinical and laboratory findings of 138 pediatric patients with growing pain and 30 healthy control subjects were examined and then the changes in pain scores of children and their families with follow-up and treatment were evaluated. The pain was most commonly seen in the form of lower extremity pain at night and in girls. Although growing pains can be treated with nonpharmacological methods, there were also patients who required pharmacological treatment. Vitamin D deficiency was observed in children with growing pain. Vitamin D treatment was given to 46 patients with vitamin D deficiency. Pain scores made by both themselves and their families decreased in 91.4% of the patients who came for control. After the use of vitamin D in children with growing pains, the mean pain score reported by the children decreased from 7.26±1.757 to 2.46±2.38. The mean pain score reported by families about their children decreased from 7.56±1.97 to 2.51±2.53 after vitamin D supplementation. Although most of the time growing pain is a self-limiting clinical picture, vitamin D supplementation may be necessary after a differential diagnosis was made because of the high level of anxiety in the families of children who do not respond to non-pharmacological approaches.
Keywords: Vitamin D; children; Growing pain